Manajemen Sumber Daya Manusia Berbasis Nilai Kepesantrenan dalam Lembaga Pendidikan: Penguatan Profesionalisme dan Keberlanjutan Kinerja Akademik - Minanulloh Muhtadi; Siti Aimah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze human resource management (HRM) based on Islamic boarding school values ​​in strengthening educator professionalism and sustaining academic performance at MA Al-Amiriyyah Blokagung. The study focuses on the process of internalizing Islamic boarding school values ​​in HRM policies and practices and their implications for educator professionalism and the sustainability of the institution's academic quality. This study uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews with madrasah leaders and educators, observations of institutional practices, and documentation studies of policies and human resource development programs. Data analysis was conducted thematically through the stages of data reduction, data presentation, and drawing conclusions. The results show that Islamic boarding school values ​​such as sincerity, service, discipline, exemplary behavior, and moral responsibility have been internalized normatively and practically in HRM policies, particularly in aspects of human resource planning, recruitment, coaching, and evaluation of educator performance. These values ​​shape educator professionalism that is not only based on pedagogical competence, but also an ethos of devotion and moral integrity. The human resource development and coaching system contributes to maintaining work motivation and consistent academic performance among educators. However, the internalization of Islamic boarding school values ​​still tends to be cultural and person-centered, and has not been fully institutionalized in written policies, standard procedures, and long-term strategic planning. Therefore, its sustainability remains dependent on leadership figures. The implications of this research emphasize the importance of strengthening the institutionalization of Islamic boarding school value-based human resource management (HRM) through formal policies, a sustainable human resource development system, and systematic managerial governance to ensure the sustainable maintenance of educator professionalism and the institution's academic performance.